2021
DOI: 10.3389/fmicb.2020.592220
|View full text |Cite
|
Sign up to set email alerts
|

A Thermostable, Modified Cathelicidin-Derived Peptide With Enhanced Membrane-Active Activity Against Salmonella enterica serovar Typhimurium

Abstract: Foodborne illness caused by consumption of food contaminated with Salmonella is one of the most common causes of diarrheal disease and affects millions of people worldwide. The rising emergence and spread of antimicrobial resistance, especially in some serotypes of Salmonella, has raised a great awareness of public health issues worldwide. To ensure safety of the food processing chain, the development of new food preservatives must be expedited. Recently, thermal- and pH-stable antimicrobial peptides have rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Rapid-responsive antimicrobial ability, which can correspond to a short response time, is a crucial factor in reducing the risks of drug resistance. Therefore, it is essential to consider both the required concentration and response time when assessing antimicrobial ability. In this section, a plate counting test was conducted to compare the antimicrobial ability of different drugs within a limited time frame.…”
Section: Resultsmentioning
confidence: 99%
“…Rapid-responsive antimicrobial ability, which can correspond to a short response time, is a crucial factor in reducing the risks of drug resistance. Therefore, it is essential to consider both the required concentration and response time when assessing antimicrobial ability. In this section, a plate counting test was conducted to compare the antimicrobial ability of different drugs within a limited time frame.…”
Section: Resultsmentioning
confidence: 99%
“…K. pneumoniae ATCC BAA-2146 has been shown to be resistant to several antibiotics [ 61 62 ] and has about 36 chromosomal and plasmid genes associated with antibiotic resistance [ 61 ], and S . enterica Typhimurium ATCC 13311 is a reference bacteria commonly used as a MDR strain [ 63 64 ]. To our knowledge, this study is the first report of MDR in Enterobacter cloacae ATCC 35030 and P2224.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the screening of six different AMPs (KLK and KLK1) derived from flesh fly larva, BmKn-2, and BmKn-22 derived from scorpion venom, and Pug-1 and Pug-4 derived from pomegranate fruit), against eight multidrug-resistant Salmonella isolates showed that BmKn-2 derived from scorpion venom has the highest and most potent antibacterial activity against all isolates and the highest inhibition of Salmonella biofilm formation compared with other peptides [321]. Another in vitro study determining the antimicrobial activity of the modified thermostable cathelicidin-derived peptide, P7, against drug-resistant S. Typhimurium showed that P7 decreased the S. Typhimurium viable cells to more than 10 3 and 10 4 cfu/mL within 2 to 4 h, respectively, and also demonstrated complete clearance of Salmonella 24 h post incubation [322]. Furthermore, it was reported that AMP (Microcin J25) could significantly reduce the infection rate of Salmonella CVCC519 by approximately 30% in challenged Arbor Acres male broiler chickens at day 42 compared to non-treated birds [183].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%